2022
DOI: 10.4194/aquast910
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance of African Catfish (Clarias Gariepinus) Fed on Diets Containing Black Soldier Fly (Hermetia Illucens) Larvae Under Aquaponic System

Abstract: Cost of fish production can be reduced by replacement of high-priced fishmeal (FM) with insects sourced ingredients. Four months feed experiment was conducted at a fish farm in Baringo County, Kenya to investigate effects of substituting fishmeal (FM) with black soldier fly larvae meal (BSFLM) on survival and growth performance of C. gariepinus under aquaponic system. Three test diets 35% crude protein content (CP) in which FM was substituted by BSFLM at 25%, 50% and 75% were formulated and experimented with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The differentiating influence between the two feed types lies in the ingredients' quality and the standardized manufacturing process. The slow growth of the maggot meal-based feed may be influenced by the unavailability of essential supplements in the © Copyright by Indonesian Aquaculture Society 2023 test feed required by the juvenile stadia (Maranga et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differentiating influence between the two feed types lies in the ingredients' quality and the standardized manufacturing process. The slow growth of the maggot meal-based feed may be influenced by the unavailability of essential supplements in the © Copyright by Indonesian Aquaculture Society 2023 test feed required by the juvenile stadia (Maranga et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The value of the feed conversion ratio is higher than the initial research of Kamalii et al, (2022), with a range of FCR values with maggot flour substitution in goldfish feed between 1.88-2.79. According to Maranga et al (2022), factors that can affect differences in feed conversion ratios include variations in feed ingredients, species type, culture system, and maintenance stocking density. The substitution of fishmeal with maggot meal gave varying results in each study.…”
Section: © Copyright By Indonesian Aquaculture Society 2023mentioning
confidence: 99%
“…Several investigations showed that the suitable percentage of FM replacement is 50%, where the BSFLM inclusion amount is 18gm, 30.8gm, 15gm, 0.53gm, 20.04gm and 21gm in 100gm of diet for pikeperch, Asian sea, rainbow trout, bass, Jian carp, common carp and zebrafish respectively (Stejskal et al, 2023;Katya et al 2017;Caimi et al, 2021;Li et al, 2017;Azizal et al, 2019;Zarantoniello et al, 2018). Fewer studies stated that the optimum FM replacement percentage is 60% (20.10gm/100 gm) for gold fish (Kamalii et al, 2022) and 75% for African catfish, climbing perch (20.63gm and 37.5gm per 100gm of diet respectively) (Maranga et al, 2022;Mapanao et al, 2021).…”
Section: Water Qualitymentioning
confidence: 99%
“…Jian) [23], yellow catfish (Pelteobagrus fulvidraco) [24], Japanese seabass (Lateolabrax japonicus) [22], mirror carp (Cyprinus carpio var. specularis) [25], Atlantic salmon (Salmo salar) [26,27], Siberian sturgeon (Acipenser baerii Brandt) [28,29], European seabass (Dicentrarchus labrax) [30], African catfish (Clarias gariepinus) [31], Nile tilapia (Oreochromis niloticus) [32], and rainbow trout (Oncorhynchus mykiss) [33,34]. However, it should be noted that the optimal amount of fishmeal that should be replaced with BSFLM depends on the fish species, and incorrect replacement could potentially have negative effects on growth, physiological processes, fillet quality, and environmental water quality [15,17,32].…”
Section: Introductionmentioning
confidence: 99%